Mission France : the true history of the women of SOE - Vigurs, Kate (Yale University Press, 2021)
The full story of the thirty-nine female SOE agents who went undercover in France
Keywords: Great Britain. -- Special Operations Executive. -- F Section.; Great Britain. -- Special Operations Executive. -- F Section; World War, 1939-1945 -- Underground movements -- France.; World War, 1939-1945 -- Secret service -- Great Britain.; World War, 1939-1945 -- Women.; Guerre mondiale, 1939-1945 -- Mouvements de résistance -- France.; Guerre mondiale, 1939-1945 -- Service secret -- Grande-Bretagne.; Guerre mondiale, 1939-1945 -- Femmes.; HISTORY / Military / World War II.; Secret service; War -- Underground movements; Women; France; Great Britain; 1939-1945